2010
DOI: 10.1103/physrevlett.104.046804
|View full text |Cite
|
Sign up to set email alerts
|

Large Increase of the Curie Temperature by Orbital Ordering Control

Abstract: Using first principle calculations we showed that the Curie temperature of manganites thin films can be increased by far more than an order of magnitude by applying appropriate strains. Our main breakthrough is that the control of the orbital ordering responsible for the spectacular T{C} increase cannot be imposed by the substrate only. Indeed, the strains, first applied by the substrate, need to be maintained over the growth direction by the alternation of the manganite layers with another appropriate materia… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

9
81
0

Year Published

2012
2012
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 95 publications
(90 citation statements)
references
References 14 publications
9
81
0
Order By: Relevance
“…This was already reported for La 0.8 Ba 0.2 MnO 3 thin films and LSMO/BTO superlattices [15,31]. Such bond angle modification does affect the electronic orbital reconstruction at the interface and thus can result in interfacial ferromagnetic states as already has been confirmed in BiFeO 3 -La 0.7 Sr 0.3 MnO 3 heterostructures by x-ray magnetic circular dichroism and scanning transmission electron microscopy [22,32].…”
supporting
confidence: 51%
See 1 more Smart Citation
“…This was already reported for La 0.8 Ba 0.2 MnO 3 thin films and LSMO/BTO superlattices [15,31]. Such bond angle modification does affect the electronic orbital reconstruction at the interface and thus can result in interfacial ferromagnetic states as already has been confirmed in BiFeO 3 -La 0.7 Sr 0.3 MnO 3 heterostructures by x-ray magnetic circular dichroism and scanning transmission electron microscopy [22,32].…”
supporting
confidence: 51%
“…This has resulted in magnetic tunnel junctions with exceptionally large tunnel magnetoresistance ratio [13]. Recently, it was shown that the T C of LSMO can be significantly enhanced by epitaxial strain in a carefully designed superlattice geometry [15]. A T C of 650 K was achieved in the LSMO/BaTiO 3 (LSMO/BTO) superlattice.…”
mentioning
confidence: 92%
“…Here, the distortions of the B O 6 octahedra at the BMO/ BFO interfaces may be not suitable for optimum magnetic coupling. [25][26][27][28] Similar effects of strongly sensitive magnetic properties to structural distortion have been observed previously in superlattices of [ 25 (SL-LSMO/BTO). Strong enhancements of T C were found in these strained superlattices, 1000 K for SL-LCMO/BTO, and 650 K for SL-LSMO/ BTO, whereas in relaxed bulk and plain thin fi lms of LCMO and LSMO lower T C s of only 250 and 370 K, respectively, were achieved.…”
Section: Doi: 101002/admi201500597supporting
confidence: 60%
“…Moreover, the lattice strain from the substrate as well as the superlattice interfaces can affect the magnetic behavior as a result of changes in orbital ordering or bonding distortion of the B O 6 octahedra. [25][26][27][28][29] Here, in SL-BFO m /BMO m ( m = 1, 2, 4, and 8 unit cells (u.c. )), tuning Fe-Mn magnetic interactions through interfacial strain and charge engineering is demonstrated.…”
Section: Doi: 101002/admi201500597mentioning
confidence: 99%
“…9,10 However, utilizing strain is a static approach to tailoring the desired orbital configuration. 21 In this Letter, we describe an approach that utilizes nanoscale ferroelectrics and enables reversibly modulating orbital occupations at La 1−x Sr x MnO 3 (LSMO, x=0.2 for the current study) interfaces. We begin with first principles calculations which show that switching the ferroelectric polarization at a (001) ferroelectric/manganite interface can modulate the atomic-scale structure, change the electronic distribution at the interface, and split the orbital degeneracy of the interfacial Mn e g levels.…”
mentioning
confidence: 99%